Determinants of Non-Compliance With use of Mask Causing a Surge in Covid-19 Cases (Case Study in Ule Village, Asakota District, Bima City-West Nusa Tenggara) - Zahratul Hayati (Universitas Muhammadiyah Palu, 2023)
Background: COVID-19 cases in the world have reached 62,162,592 cases. Based on the Worldometers report, Indonesia is still in the top 10 with the highest number of cases in Asia. In West Nusa Tenggara itself, it is ranked 2nd best in the COVID-19 recovery index, but this does not rule out the possibility that there could be a spike in cases. Objective: to analyze the main factors causing the lack of public awareness in using masks during the COVID-19 pandemic in Ule Village, Asakota District, Bima City. Method: This research is a case study research with a cross sectional design. The population in this study is all the people who live there in Ule Village, Asakota District, Bima City. Results: As many as 55.9% were in a state of non-compliance with the use of masks because it was difficult to breathe (stuffy), they did not believe that Covid-19 was real, there was no need to use a mask if they only left the house for a short distance, it could hinder communication with the POR value = 37,424 (p.value < 0.05) so that the risk of transmission of COVID-19 could occur 37 times in people who do not comply with wearing masks when compared to people who comply with wearing masks. Conclusion: The main factor causing the lack of public awareness regarding the use of masks during the COVID-19 pandemic is that there are still people who feel that using a mask can hinder communication and feel that using a mask causes difficulty in breathing.